Calls to action - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
ASSESS PROGRESS AGAINST GLOBAL TARGETS; MAKE SMART COMMITMENTS; ACCELERATE IMPLEMENTATION; ACCELERATE THE CONTRIBUTION OF THE UNDERLYING DRIVERS; FINANCE THE GLOBAL TARGETS; MEASURE PROGRESS AT THE NATIONAL AND SUBNATIONAL LEVEL